PRE-SERVICE TEACHERS' TRAINING FOR THE INNOVATIVE EXTRACURRICULAR WORK - Nataliia Onyshchenko; Nataliia Serdiuk; Valentyna Krykun (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2021)
The research proves that the level of pre-service teachers' readiness for innovative extracurricular work at school will be increased together with the general index of their satisfaction with the extracurricular work at university after the implementing the designed holistic program of their training. The participants of the pedagogical experiment were 148 students, divided into experimental and control groups; the experts were 18 teachers of Philological Faculty of the Hryhorii Skovoroda University in Pereiaslav and 10 General Secondary Schools teachers (Pereiaslav, Ukraine). After implementation of the program, 27% of participants were ready for innovative extracurricular work at the high level, 62% of students increased their level of readiness for innovative extracurricular work to the middle one. The suggested program also increased the students' satisfaction with the extracurricular work at university. On the basis of the research results, the authors suggest methodical recommendations for educators.